Bibliometric Mapping Analysis of Scientific Publications in Chemistry Field on Cerium Oxide Nanoparticles Using Vosviewer - Anisa Klarasita; Asep Bayu Dani Nandiyanto; Tedi Kurniawan (Universitas Pakuan, 2022)
This study aims to look at the advancement of scientific publications related to cerium oxide nanoparticles through a bibliometric approach using qualitative methods with descriptive statistics on literature studies on scientific articles. Two types of software are used: Publish or Perish and VOSviewer. Publish or Perish is used as a source to search for various relevant articles through the Google Scholar database, using the keyword